The Effect of Combining Physical Education Lesson with Mathematics on Learning Basic Skills of Students - Horieh Hajirostamlo; Alimohammad Amirtash; Alimohammad safania (پژوهش در نظام‌های آموزشی, 2020)
In a constantly changing environment, education and training systems are responsible for the future development and development of the country, one of the things that has attracted much attention in education is the health and basic skills of students. Given the importance of basic skills and the rarity of studies related to physical education integration in other courses, this study uses a quantitative research in a quasi-experimental design to investigate the effect of integrating physical education course with math lesson on learning skills. Students fundamentals. For this purpose, using cluster sampling method, a sample of 30 female second grade elementary school students in Khoy city was used as the participants. For the purpose of the study, the students in the experimental group (n = 15) performed the physical education activities in combination with the math lesson, while the control group (n = 15) students studied in the same traditional way. The study was performed for ten weeks, each 45 minutes. Statistical analysis of data using the Mann-Whitney U test and independent t-test indicated that performance in the basic skills of the experimental group was better than the control group at the end of the period. These findings can have significant theoretical and practical implications for the integration of a physical education lesson with mathematics into the students' fundamental skills.